A biomechanical study of the role of sitagliptin on the bone characteristics of diabetic rats (Fracture and Structural Integrity, 2019)
An experimental protocol is described aiming to explore the influence of Type 2 Diabetes Mellitus on the biomechanical response of the bone tissue and, also, to quantify the potential beneficial role of a pharmaceutical treatment, based on sitagliptin, a diabetes drug that increases the levels of natural substances called incretins. Twenty eight male, 10-week old Wistar rats were used, divided into three groups, i.e., the control one, the group including the diabetic rats and, finally, the group including the diabetic rats which were treated using sitagliptin. The biomechanical study was based on a series of three-point bending tests of the femora of the sacrificed rats and the analysis of the experimental data was implemented in terms of the actual geometry of the fractured cross-section. It was concluded that diabetic bones undertake larger forces despite the fact that the “diameter” of their cross-section was somehow smaller. On the contrary, the slope of the load-deflection curve (corresponding to a measure of the stiffness) of diabetic bones is slightly lower compared to the control bones. Finally, it seems that treating diabetic animals with sitagliptin only partly reverses the effect of Type 2 Diabetes Mellitus on their bone tissue, at least concerning its strength and stiffness.
Keywords: Male Wistar rats; Type-2 diabetes; Sitagliptin; Biomechanics; Three point bending; Video-extensometer